Experiences, health needs, and access to health services of university students with female circumcision: A qualitative study - Evrenol Öçal, Simge; Şimşek Çetinkaya, Şahika (Wiley, 2024)
AbstractAimsThis study aimed to assess the female circumcision (FC) experiences, healthcare needs, and access to health services of foreign university students who are victims of female genital mutilation and studying in Turkey.MethodsThis descriptive qualitative study was conducted in the Faculty of Health Science in a state university in Turkey from December 2021 to January 2022. Eight students who had been subjected to FC participated in this study. Data were collected by conducting in‐depth, semistructured online interviews and using a pilot‐tested interview guide. The data were analyzed using inductive thematic analysis.ResultsFour themes emerged: “reasons for performing FC, ‘health effects of FC,’ ‘psychological problems linked to FC,’ and ‘FC survivors' access to health services.’” Students stated that they exposed to this practice because of limiting their womanhood, they experienced problems, such as pelvic pain, infection, loss of sexuality, fear of pregnancy and birth, and they had healthcare needs due to FC but face some barriers.ConclusionsFC negatively affects women's health and has specific healthcare needs. Studying in a different country can be turned into an opportunity to solve the health problems they experience. For this, the right approach with knowledgeable and culturally sensitive health professionals can change stereotypes towards practice.
Keywords: Adult; Young Adult; Health Services Needs and Demand; Universities; Turkey; Circumcision, Female; Humans; Female; Students; Health Services Accessibility; Qualitative Research